Strategi Guru Fikih dalam Menggunakan Media Pembelajaran Berbasis Information and Communication Technology (ICT) di MTsS Hubbul Wathan Modal Bangsa Sei Bingai - Haidir, Haidir; Baiti, Nanda Nurul; Manalu , Sri Rahmayani; Frarera, Andre Nova; Harahap, Yudhi Septian; Anwar, Hairil (EduInovasi: Journal of Basic Educational Studies, 2024)
The teacher uses teaching strategies to ensure that learning goes well, efficiently, and optimally. After evaluating, the teacher follows up to achieve the minimum mastery standards for students. This research aims to explain how teachers use teaching strategies in the classroom, focusing on class IX at MTsS Hubbul Wathan Modal Bangsa. The research obtained data through interviews and observations in class IX with several PAI subject teachers. The data validation method used is the triangulation technique. The data analysis technique consists of data reduction (data selection), data presentation (data display), and then drawing conclusions/verification. The results of the study show that the teacher's teaching has been proven to be efficient, effective, and optimal, with a well-organized learning process, good student understanding, and the use of IT-based media that helps students understand the material.